Adherence to antihypertensive treatment during the COVID-19 pandemic: findings from a cross-sectional study - Mayra Cristina da Luz Pádua Guimarães; Juliana Chaves Coelho; Juliano dos Santos; Camila Braga de Oliveira Higa; Carime Farah Flórido; Renata Jae Won Lee; Grazielli Soares Paes; Giovanio Vieira da Silva; Luciano Ferreira Drager; Angela Maria Geraldo Pierin (Clinical Hypertension, 2022)
Abstract Background Nonadherence to antihypertensive treatment is one of the main causes of the lack of blood pressure (BP) control. The coronavirus disease (COVID-19) pandemic imposes substantial social restriction impairing the medical care routine, which may influence adherence to the antihypertensive treatment. To assess the rate of nonadherence to antihypertensive drug treatment during the COVID-19 pandemic. Methods This is a cross-sectional study evaluating hypertensive adult patients from a tertiary outpatient clinic. From March to August 2020, patients were interviewed by telephone during the social distancing period of the COVID-19 pandemic. We evaluated biosocial data, habits, attitudes, and treatment adherence using the 4-item Morisky Green Levine Scale during the social distancing. Uncontrolled BP was defined by BP ≥ 140/90 mmHg. Clinical and prescription variables for drug treatment were obtained from the electronic medical record. We performed a multivariate analysis to determine the predictors of nonadherence to BP treatment. Results We studied 281 patients (age 66 ± 14 years, 60.5% white, 62.3% women, mean education of 9.0 ± 4 years of study). We found that 41.3% of the individuals reported poor adherence to antihypertensive drug treatment and 48.4% had uncontrolled BP. Subsample data identified that adherence was worse during the pandemic than in the previous period. The variables that were independently associated with the nonadherence during the pandemic period were black skin color (odds ratio [OR], 2.62; 95% confidence interval [CI], 1.46–4.68), and intermittent lack of access to antihypertensive medication during the pandemic (OR, 2.56; 95% CI, 1.11–5.89). Conclusions Beyond traditional variables associated with poor adherence, the lack of availability of antihypertensive medications during the study underscore the potential role of pandemic on hypertension burden.